The influence of public university student leadership on democratization education in Malaysia - Safian, Anuar; Ibrahim, Abdullah; Md Rami, Ahmad Aizudin; Wan Mokhtar, Wan Khairul Aiman; Mohd Ghazalli, Farah Syazrah; Mat Saad, Khoirun Nisak (Macrothink Institute, 2022)
Malaysia's progress depends on the effectiveness of leaders in maintaining unity based on the principles of Rukun Negara and upholding the existing law. The development of democratization education is extremely important to ensure the well-being of our beloved Malaysia. This process must take place perfectly for the well-being of Malaysian citizens towards continuing to lift the country's progress in the future. Students are the front line of the country on their shoulders carrying the trust of leadership and the future of the country. They play an important role as future leaders and need to have a high level of understanding and appreciation of democratization and duty as Malaysians. Specifically, this research examines the impact of student leadership on the democratization of education in Malaysian public universities. The student leadership questionnaire developed by Kouzes & Posner in 2007 and the democratized education questionnaire developed by Evans & Rose in 2007 adopted a cross-sectional survey method in the data collection process. A total of 326 student leaders of Peninsular Malaysia Public University participated as the study’s Respondents. Student leadership has also had a 39.6% impact on democratized education. This research can be used by national leaders, university administrations, and the Ministry of Education as a guide for assessing the leadership of future national leaders. It can be used as a basic reference to improve various knowledge of leadership management based on democratization education as the basis for the formation of the identity of Malaysian leaders.